Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1047
|View full text |Cite
|
Sign up to set email alerts
|

NORMA: Neighborhood Sensitive Maps for Multilingual Word Embeddings

Abstract: Inducing multilingual word embeddings by learning a linear map between embedding spaces of different languages achieves remarkable accuracy on related languages. However, accuracy drops substantially when translating between distant languages. Given that languages exhibit differences in vocabulary, grammar, written form, or syntax, one would expect that embedding spaces of different languages have different structures especially for distant languages. With the goal of capturing such differences, we propose a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…We build on (Kumar and Tsvetkov, 2019), one of the first instances of using pretrained embeddings as model outputs for complex sequencegeneration tasks. Closely related work on embedding prediction includes zero-shot learning for word translation (Nakashole, 2018;Conneau et al, 2018) and image labeling (Lazaridou et al, 2015), as well as rare word prediction (Pinter et al, 2018) and classification (Card et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…We build on (Kumar and Tsvetkov, 2019), one of the first instances of using pretrained embeddings as model outputs for complex sequencegeneration tasks. Closely related work on embedding prediction includes zero-shot learning for word translation (Nakashole, 2018;Conneau et al, 2018) and image labeling (Lazaridou et al, 2015), as well as rare word prediction (Pinter et al, 2018) and classification (Card et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…In addition, recent work has leveraged topological similarities between monolingual vector spaces to introduce fully unsupervised projectionbased CLE approaches that do not require any bilingual supervision (Zhang et al, 2017;Conneau et al, 2018a;Artetxe et al, 2018b;Alvarez-Melis and Jaakkola, 2018). Being conceptually attractive, such weakly supervised and unsupervised CLEs have taken the field by storm recently (Conneau et al, 2018a;Dou et al, 2018;Doval et al, 2018;Hoshen and Wolf, 2018;Kim et al, 2018;Chen and Cardie, 2018;Mukherjee et al, 2018;Nakashole, 2018;Xu et al, 2018;Alaux et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the main success of these methods was obtained on linguistically similar languages where a large volume of monolingual data from compatible sources is available. A recent study showed that a simple linear mapping is not enough for low resourced languages (Nakashole, 2018). However, the proposed method in this study, NorMA, came short in solving the problem showing significant gains in mapping precision for Russian-English and Chinese-English, compared not to the best model in (Lample et al, 2018), while underperforming in Spanish-English French-English and German-English.…”
Section: Introductionmentioning
confidence: 67%
“…In low resourced languages with a significantly lower amount of data compared to the English corpora structural similarities of the two spaces are not guaranteed leading to weak initial assumptions. This is also true in languages with lower similarity to English such as Slavic and Asian languages (Nakashole, 2018;Nakashole and Flauger, 2018). Nakashole and Flauger showed that word neighborhoods require different linear mappings to correctly capture the word relation.…”
Section: Intuitionmentioning
confidence: 97%
See 1 more Smart Citation